Impact of the national rotavirus vaccination programme on acute gastroenteritis in England and associated costs averted. Issue 4 (23rd January 2017) - Thomas, Sara L.; Walker, Jemma L.; Fenty, Justin; Atkins, Katherine E.; Elliot, Alex J.; Hughes, Helen E.; Stowe, Julia; Ladhani, Shamez; Andrews, Nick J.
Highlights: Acute gastroenteritis primary care visits fell sharply after vaccine introduction. Decreases were most marked in the age groups targeted for vaccination. Decreases were also seen in older children and adults, indicating herd immunity. An estimated 87, 376 healthcare visits by young children were averted. There was an estimated £12.5 million reduction in healthcare costs across settings. Abstract: Background: Introduction of infant oral rotavirus vaccination in the UK in July 2013 has resulted in decreased hospitalisations and Emergency Department (ED) visits for acute gastroenteritis (AGE), for both adults and children. We investigated reductions in AGE incidence seen in primary care in the two years after vaccine introduction, and estimated the healthcare costs averted across healthcare settings in the first year of the vaccination programme. Methods: We used primary care data from the Clinical Practice Research Datalink and age-stratified time-series analyses to derive adjusted incidence rate ratios (IRRa ) for AGE in the first two years of the post-vaccination era (July 2013-April 2015) compared to the pre-vaccination era (July 2008-June 2013). We estimated cases averted among children aged <5 years in the first year of the vaccination programme by comparing observed numbers of AGE cases in 2013–2014 to numbers predicted from the time-series models. We then estimated the healthcare costs averted for general practice consultations, ED visits and hospitalisations. Results: In general practice, AGE rates in infants (the target group for vaccination) decreased by 15% overall after vaccine introduction (IRRa = 0.85; 95%CI = 0.76–0.95), and by 41% in the months of historically high rotavirus circulation (IRRa = 0.59; 95%CI = 0.53–0.66). Rates also decreased in other young children and to a lesser degree in older individuals, indicating herd immunity. Across all three settings (general practice, EDs, and hospitalisations) an estimated 87, 376 (95% prediction interval: 62, 588–113, 561) AGE visits by children aged <5 years were averted in 2013–14, associated with an estimated £12.5 million (9, 209–16, 198) reduction in healthcare costs. Conclusions: The marked decreases in the general practice AGE burden after rotavirus vaccine introduction mirror decreases seen in other UK healthcare settings. Overall, these decreases are associated with substantial averted healthcare costs.